2015
DOI: 10.1097/nan.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Intermittently Delivered IV Medication and pH

Abstract: The Infusion Nurses Society's Infusion Nursing Standards of Practice has treated pH as a critical factor in the decision-making process for vascular access device selection, stating that an infusate with a pH less than 5 or greater than 9 is not appropriate for short peripheral or midline catheters. Because of the Standards, drug pH is not an uncommon factor driving the decision for central vascular access. In this era of commitment to evidence-based practice, the pH recommendation requires reevaluation and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…Guidelines for administration of intravenous medication (RCN, 2016) recommend that CVC should be considered for the administration of drugs such as epirubicin with a low pH (<5) which are thought to have an increased potential for causing chemical phlebitis. However, the evidence base for this guidance has been questioned by Gorski, Hagle, and Bierman (2015) who concluded that the pH of the drug cannot be used in isolation as basis for using a CVC. Yamada et al (2012) in their study of epirubicin-induced vascular injury also state that the mechanism of epirubicin-in- *p = <0.05 chi-square test: Group 2 compared with Groups 1 and 3, otherwise no significant differences were observed between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for administration of intravenous medication (RCN, 2016) recommend that CVC should be considered for the administration of drugs such as epirubicin with a low pH (<5) which are thought to have an increased potential for causing chemical phlebitis. However, the evidence base for this guidance has been questioned by Gorski, Hagle, and Bierman (2015) who concluded that the pH of the drug cannot be used in isolation as basis for using a CVC. Yamada et al (2012) in their study of epirubicin-induced vascular injury also state that the mechanism of epirubicin-in- *p = <0.05 chi-square test: Group 2 compared with Groups 1 and 3, otherwise no significant differences were observed between groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence base for this guidance has been questioned by Gorski, Hagle, and Bierman (2015) who concluded that the pH of the drug cannot be used in isolation as basis for using a CVC. However, the evidence base for this guidance has been questioned by Gorski, Hagle, and Bierman (2015) who concluded that the pH of the drug cannot be used in isolation as basis for using a CVC.…”
Section: Discussionmentioning
confidence: 99%
“…Values of pH lower than 5.5 and higher than 8.0 represent risks of complications during intravenous therapy. (17) Amiodarone has pH between 3.8 and 4.0, so it is a drug with potential risk to the impairment of the vessel. Forms of amiodarone administration, which relate to the respective variations in the vein exposure time, should be taken into consideration and may justify the non-occurrence of phlebitis in puncture groups that received exclusive bolus infusion and the occurrence of the event in the other groups analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Pengujian pH pada sediaan perlu dilakukan karena dapat memengaruhi kelarutan dan stabilitas obat. 40 Kualitas sediaan racikan injeksi seftriakson hasil racikan RS "X" memiliki kualitas yang sama dengan yang terdapat dari literatur baik dari segi warna, pH, dan kejernihan. Sediaan parenteral harus bebas dari mikroorganime.…”
Section: Observasiunclassified